Cost-benefit analysis of on-farm management of improved forage varieties in western Kenya - Karimi, Peggy; Ugbede, Joseph; Enciso, Karen; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2022)
Yield of forages is influenced by several factors including climate and soil. The heterogeneity presented in each site leads to the varying yields of forages. As a result, sites with better soils and climate have higher yields, subsequently higher profitability. Each forage variety is suited and performed better in different agro ecological zones. This explains the differences in profitability index among Panicum and Brachiaria in different sites. From an economic perspective, experts are able to describe and recommend the best forage varieties per region where they indicate best profitability. Those farmers who practiced better agronomic practices increased the potential of forage yields and subsequently achieved good profitability indicator values across all four sites. In contrast, poor management of forage plots reduced yields, and overall benefits accrued from forage cultivation. Dried forage (hay) had better profitability economic indicators compared to those from fresh forage. This is a result of the better prices offered and the market level for hay. Hay returns for most farmers were sufficient to cover the financial investments and cost incurred by farmers across the four sites for all varieties.